A look at corporate social responsibility and firm performance : evidence from South Africa - Demetriades, Kimon (My University, 2011)
Corporate Social Responsibility (CSR) is a new topic in finance which can be viewed from two different perspectives: that of the business (CSR), and that of the individual investor (Socially Responsible Investing, SRI). The evidence from this study suggested that in the short-term, there were no significant price effects on the SRI stocks around the announcement dates of the SRI constituent lists. In contrast, the returns of SRI portfolios over the sample period seemed to be superior to those of conventional firms. The regression analysis found that generally the SRI coefficients were insignificant; however using one of the models during the fifteen year period, it was found that SRI constituents attained a ROE that was 11.18% higher than conventional peers as well as a ROA that was 1.824% lower than conventional firms. When the period was restricted to 2004-2009 it was found that social performance was positively (and sometimes significantly) correlated with ROE.
Keywords: Corporate social responsibility; Socially responsible investing; Financial performance